Effect of planting patterns and weed management on weed suppression, productivity and economics of African mustard (Brassica carinata) and Indian mustard (Brassica juncea) intercropping - RANA, D S (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during the winter seasons of 1999-2001 to assess the feasibility of intercropping African mustard (Brassica carinata A. Braun) and Indian ITIustard Brassica juncea (L.) Czemj & Cosson under 6 planting patterns and 3 weed managenlent practices. Pre-emergence application of pendimethalin @ 1 kg/ha or 1 hand weeding at 20 days after sowing effectively controlled the weeds and demonstrated a significant increase in seed yield of component crops system seed yield and net returns over weedy check. Among the weed control treatments, 1 hand weeding at 20 days after sowing proved better in all respect than the pendimethalin and gave 18.6 and 8.3 % higher seed yield of component crops. Sole Indian mustard recorded higher weed control efficiency and suppressed weed count by 12.2 ern and weed dry mass by 29.4 %over the sole African mustard. Contrary to this, African mustard gave significantly higher seed yield (2.51 tonnes/ha) and net returns (Rs18 020/ha) that were 9.6 and 13.9 % higher than the sole Indian mustard. Intercropping systems significantly reduced the weed count and weed dry weight compared to sole stand. Among the intercropping systcnlS, paired row planting at 45/1 05 em in 2:2 row ratio gave the highest total seed yield (2.82 tonnes/ 11a), LER (1.18), net returns (Rs 21 220/ha) and benefiteost ratio (3.84), which were 14.3, 18.0, 17.7 and 11.8 % higher than sole African mustard.